Coffee component hydroxyl hydroquinone (HHQ) as a putative ligand for PPAR gamma and implications in breast cancer - Shashni, Babita (BioMed Central, 2013)
BACKGROUND: Coffee contains several compounds that have the potential to influence breast cancer risk and survival. However, epidemiologic data on the relation between coffee compounds and breast cancer survival are sparse and inconsistent. RESULTS: We show that coffee component HHQ has significant apoptotic effect on MDA-MB-231 and MCF-7 cells in vitro, and that ROS generation, change in mitochondrial membrane permeability, upregulation of Bax and Caspase-8 as well as down regulation of PGK1 and PKM2 expression may be important apoptosis-inducing mechanisms. The results suggest that PPARγ ligands may serve as potential therapeutic agents for breast cancer therapy. HHQ was also validated as a ligand for PPARγ by docking procedure. CONCLUSION: This is the first report on the anti-breast cancer (in vitro) activity of HHQ.